Membangun Identitas Merek dalam Street Photography: Analisis Strategi Pemasaran Digital - Muliatie, Yurilla Endah; Jannah, Nur; Suprapti, Sri (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study aims to analyze the digital marketing strategies employed by street photographers in building their brand identity in the digital era. Using a descriptive qualitative approach, data were collected through in-depth interviews with both professional and amateur street photographers, as well as netnographic observation on social media platforms such as Instagram and YouTube. The findings reveal that street photographers who successfully establish a strong brand identity tend to implement consistent and authentic content strategies while engaging with their audience through personal and emotional storytelling behind each photo. Instagram is identified as the primary platform for visibility, while YouTube offers broader opportunities to share stories about the creative process. Photographers who maintain authenticity and consistency in their visual style tend to attract more loyal followers, despite facing the challenge of balancing commercial demands with artistic integrity. In conclusion, the success of building a street photographer's brand identity in the digital space depends on a combination of visual quality, authentic narratives, and meaningful engagement with the audience. This study highlights the importance of maintaining a balance between commercial needs and personal identity in digital marketing strategies.